A Hundred Years after the 1917 October Revolution: Imperialism, War, and Revolution Today†. Issue 4 (1st October 2016) - Michael-Matsas, Savas
Abstract : A hundred years ago, a historical sequence of imperialism, war, and revolution climaxed in the epoch-defining event of the 1917 October Socialist Revolution in Tsarist Russia. On the eve of the centenary of this unprecedented breakthrough in world history, humanity sees imperialism and wars re-affirm themselves dramatically, from the early 21st century up to today. The crucial question remains on the 'third term' of the historical sequence: will the ongoing tragedies of imperialism and war meet the redeeming moment of a revolutionary catharsis?